2016
DOI: 10.1371/journal.pone.0165751
|View full text |Cite
|
Sign up to set email alerts
|

Tithonia diversifolia as a Supplementary Feed for Dairy Cows

Abstract: The objective of this study was to examine the effects of Tithonia diversifolia as a supplementary forage on dairy cow performance and methane production. Nine lactating Holstein × Zebu dairy cows (519 ± 53.3 kg of body weight and 66 ± 13.3 d in milk) were paired by milk yield (21.3 ± 2.34 kg/d) and body weight and randomly assigned to three dietary treatments in a Latin square design with 21-d experimental periods (14 d for diet adaptation and 7 d for measurements and sample collection). The dietary treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 35 publications
(42 reference statements)
2
28
1
9
Order By: Relevance
“…A commercial calorimetry kit (Sigma Diagnostics, St. Louis, MO) was used to analyze milk samples for urea-N. Milk FA composition was determined as described elsewhere (26). The Kjedahl method (AOAC, method 954.01) was used to determine fecal N content and total fecal production was estimated by the insoluble ash technique (27).…”
Section: Methodsmentioning
confidence: 99%
“…A commercial calorimetry kit (Sigma Diagnostics, St. Louis, MO) was used to analyze milk samples for urea-N. Milk FA composition was determined as described elsewhere (26). The Kjedahl method (AOAC, method 954.01) was used to determine fecal N content and total fecal production was estimated by the insoluble ash technique (27).…”
Section: Methodsmentioning
confidence: 99%
“…An in vivo study was conducted at UFSJ to determine the effects of replacing sugarcane fresh and concentrate (DM basis) with T. Diversifolia fresh fed (0, 6.4, 15.3%) to lactating cross breed dairy cows. 7 The results found by the authors indicated that it is possible to replace sugarcane (20% DM basis) and concentrate (11.2% DM basis) in a total mixed ration diet fed to dairy cows without any change in total intake (18.7kg MS/day), milk yield (22.9kg/day) and composition. In addition, glucose, urea, triglycerides, cholesterol, non-esterified fatty acids and ß-hydroxybutyrate blood parameters were not negatively affected by the inclusion of T. Diversifolia.…”
Section: Feeding Dairy Cows With T Diversifolia -Brazilian Experiencesmentioning
confidence: 98%
“…An in vivo study was conducted at UFSJ to determine the effects of replacing sugarcane fresh and concentrate (DM basis) with T. diversifolia fresh fed (0, 6.4, 15.3%) to lactating cross breed dairy cows [7]. The results found by the authors indicated that it is possible to replace sugarcane (20 % DM basis) and concentrate (11.2 % DM basis) in a total mixed ration diet fed to dairy cows without any change in total intake (18.7 kg MS/ day), milk yield (22.9 kg/day) and composition.…”
Section: Feeding Dairy Cows With T Diversifolia -Brazilian Experiencesmentioning
confidence: 99%
“…Although it has been used as a fodder for animal nutrition [4,7,8,14], there are several uses reported for T. diversifolia like insect repellent and negative effect against ants [15], allelopathic effect against other plants [16,17], source of nectar for bees [18] and sources of nutrients (N, P and K) for degraded soils as the biomass is quickly decomposed and consequently nutrients are easily released to the soil [2,19].…”
mentioning
confidence: 99%